A situational review of infant and young child feeding practices and interventions in Viet Nam - Nguyen, Phuong Hong; Menon, Purnima; Ruel, Marie T.; Hajeebhoy, Nemat (2011)
Sub-optimal infant and young child feeding (IYCF) practices are likely a significant contributor to high undernutrition rates in Viet Nam. To date, however, there has been no comprehensive review of IYCF practices in Viet Nam. The objectives of this paper were to review: 1) patterns/trends in IYCF in Viet Nam; 2) the barriers and facilitators to IYCF practices; and 3) interventions and policies and their effectiveness. Methods used include reviewing and analyzing existing data, summarizing and organizing the evidence into broad themes based on a pre-defined conceptual framework. Findings show that the proportion of children ever breastfed is almost universal and the median duration of breastfeeding is 13-18 months. However, exclusive breastfeeding for the first six months is low (8-17%) and appears to be declining over time. Information on complementary feeding is limited, but two key challenges are: early introduction, and low nutrient quality of complementary foods. Facilitators of optimal IYCF were support from 1) government progressive policies, 2) non-profit organizations and 3) family members. Barriers to optimal IYCF included 1) the lack of enforcement of, and compliance with the code of marketing breast milk substitutes, 2) inadequate knowledge among health care providers; and 3) maternal poor knowledge. These findings indicate that the evidence base on complementary feeding is weak in Viet Nam and needs to be strengthened. The review also reinforces that program and policy actions to improve IYCF in Viet Nam must target multiple stakeholders at different levels: the family, the health system and the private sector.